Echoes of the sea - Eden, Sarah M. (Eden, Sarah M. Storm tide romance, 2025)
"For Kipling Summerfield, the glamour of Hollywood is becoming a distant memory. After losing the role of a lifetime, he's forced to take a lesser job as a historical reenactor on England's Guilford Island. But a sudden storm changes everything, casting him into the ocean -- and into the care of a mysterious lighthouse keeper. Kip assumes the island's immersive historical setting is part of an elaborate performance, though the method actors are too convincing, the details too vivid -- almost like they believe they are in 1803. But then he meets Miss Amelia Archibald, a determined and captivating woman whose quiet strength is more than just acting, and it makes him question everything he believes about Guilford. Amelia has spent her life as an unimportant poor relation and is now trapped by her late grandfather's will on an island she loathes because of her great fear of the sea, forced to restore the crumbling estate there to claim her inheritance or lose it all and her freedom to her uncle if she fails. When Kip stumbles into her world, his strange ideas and warm presence are both a disruption and an unexpected light. As Kip and Amelia work to save Guilford Island, an undeniable connection blooms between them. But when Kip uncovers the truth about where -- or when -- he is, he must make an impossible choice: rise to meet the expectations of Amelia's world and build a life worthy of her station or walk away from the love that has redefined his very existence."--